Perbandingan Pengukuran Radius Lengkung Dengan Menggunakan Benang, Total Station Dan Messreg CLS - Adi, Wahyu Tamtomo; Atmaja, Dadang Sanjaya (Politeknik Perkeretaapian Indonesia Madiun, 2018)
An examination of the railroad curves that have been operated can be done with a variety of available gauges, however there has never been a comparison of the outputs of several gauges used to check rail curves. This study intends to examine the curvature of the railroad by comparing the results of measuring arrows manually and the use of digital measuring stations and Messreg CLS. This study also tries to provide recommendations on arch maintenance plans so that the arch conditions can be optimized for trains to pass. The measurement results show that manual curvature measurements (arrows thread) with digital measuring devices (total station and CLS messeg) give results that vary from one another, although not significantly different. The measurement results with Total Station and Messreg CLS show an average value that is greater than the measurement results using Arrows thread. The results of the inspection also showed that in order to make the railroad curvature more ideal for passing trains, it was necessary to move both in and out so that the value of the Arrows at each measured point approached the ideal value of 630 mm.